The Strategic Role of School Counselors in Guiding Students to Face Peer Pressure at SMA Negeri 4 Kupang - Enjelita Minding; Matilda Pia Bone (The Future of Education Journal, 2025)
This study aims to understand the strategic role of school counselors (BK) in guiding students to face peer pressure at SMA Negeri 4 Kupang. Peer pressure is a significant social challenge in adolescent development, especially in a school environment that is socially and culturally heterogeneous. This research uses a qualitative approach with a case study design, allowing for an in-depth exploration of the experiences and strategies of school counselors in the social context of the school. Data were collected through semi-structured interviews, participatory observation, and documentation, with participants consisting of three school counselors, five students, and two class teachers, selected using purposive and snowball sampling techniques. The findings reveal three main themes: (1) school counselors as facilitators in strengthening students' social character, (2) school counselors as mediators in peer conflicts, and (3) school counselors as reflective companions in students' moral decision-making. These three roles highlight the contribution of school counselors not only in preventing negative behaviors but also in fostering social awareness, empathy, and critical thinking skills in students in response to social pressures in their environment. Theoretically, this research reinforces the concept of a humanistic approach in guidance and counseling, while practically offering implications for improving the competence of school counselors in managing students' social dynamics. The findings also encourage educational policies to strengthen the role of counseling services in building an inclusive and supportive school culture. Future research is recommended to explore the influence of cultural factors and the school’s social structure on the effectiveness of the school counselor's role in various local contexts in Indonesia.